Urban greenspaces reduce the community specialization of soil nematodes - Justin Louis Kafana Coulibaly; Xin Gong; Yuanhu Shao; Huayuan Shangguan; Alexis Kayiranga; Ismail Koné; Yanjiang Cai; Xin Sun (Geoderma)
Urbanization converts natural lands into anthropogenic-disturbed soils, which can dramatically influence soil biota. However, how urbanization influences patterns of soil biodiversity and the effects on habitat sensible groups, generalist and specialist species, are poorly understood. Here, we examined the responses of diversity and community composition of soil nematodes, the most abundant metazoans on Earth, to several urban land use types (i.e., forests, farmlands, green belts, hospitals, industrials, urban parks, and residential areas) related to urbanization. We found moderate effects of land use and its associated variables on patterns of species richness, but more dramatic changes in the abundance of habitat specialists versus generalists. Specifically, while specialists tended to be reduced, primarily due to an increase in soil pH, generalists were robust to land use changes, buffering the overall effect on the overall nematode diversity. Furthermore, our results showed that human density, as a proxy of urbanization intensity, was linked to changes in soil pH between land use types. Our results suggest that urbanization could influence the community composition of soil nematodes by favoring generalists over specialists. Together, these findings highlight the importance of understanding and considering the ecological consequences of urbanization on soil microfauna specialization in light of the urban land use management.